Mosa sebuah Upacara Peningkatan Sraddha Bhakti - I Wayan Titra Guna Wijaya (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
The Mosa ceremony is believed by the people of Pakraman Serai Village as a protector from things that make people suffer. The study of the Mosa ceremony is intended so that the community has an understanding and improves the community's sraddha bhakti from the implementation of the Mosa ceremony, through a qualitative approach and sourced from primary and secondary data which are then presented in the form of a qualitative description. The Mosa Ceremony is a series of yajna ceremonies held at Baleagung Temple located in Pakraman Serai Village. The form of implementation is adjusted to the traditions that have been inherited by the community from generation to generation, whether it is a series of ceremonies, infrastructure, prayers, series, leaders and so on. Starting from the Ngapitu ceremony, Piuning Jagi Maboros. Makarya Sanggah Pausya (Mosa), Puncak Karya, Puniki Kemargiang Ring Purnamaning Kapat ceremony, Sato War, Nyineb Ceremony, Seclusion, Nyelamping Ceremony and finally the Ngaturan Ceremony. The function of the Mosa Ceremony at Bale Agung Temple, which is located in the village of Pakraman Serai, serves to worship the greatness of God in his manifestations in order to provide safety, prosperity because he is the source of life for the community. In addition to having a theological function, it also has communication, especially formal communication which is practiced during the Dewa Yajna Mosa ceremony, verbal communication, namely when the practice occurs.Keywork: Eksistensi, Mosa Ceremony, Sraddha dan Bhakti